2022
DOI: 10.1007/s40121-022-00736-3
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lactate and 28-Day Mortality in Elderly Patients with Sepsis: Results from MIMIC-IV Database

Abstract: Introduction This study aimed to explore the association of serum lactate with clinical outcomes in elderly patients with sepsis based on data from the MIMIC-IV database. Methods All elderly patients with sepsis (age ≥ 65 years) were included. Different models were constructed for exploring the relationships between lactate and 28-day mortality. A two-segment linear regression model was performed to verify the threshold effects of lactate on clinical outcomes and smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Blood lactate levels are important predictors of severity and prognosis in human sepsis (8,10). Although sepsis experimental studies often assay blood lactate, most assay it in only one time point or as an indicator that the animal is septic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood lactate levels are important predictors of severity and prognosis in human sepsis (8,10). Although sepsis experimental studies often assay blood lactate, most assay it in only one time point or as an indicator that the animal is septic.…”
Section: Discussionmentioning
confidence: 99%
“…Blood lactate levels are important predictors of severity and prognosis in human sepsis (8,10). Although sepsis experimental FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large retrospective study found that lactate ≥ 4 mmol/l was not only associated with short-term prognosis of sepsis, but also with 1-year mortality [44]. The higher the level of lactate was, the higher the risk of 28-day mortality in elderly patients with sepsis was [45]. Isolated hyperlactatemia has been shown to increase the risk of 90-day mortality in sepsis patients by 1.7 times [46].…”
Section: Discussionmentioning
confidence: 99%
“…We selected the first set of parameters if the included variables were measured more than once in 24 h 18 , 19 . In addition, we excluded covariates with missing values ≥ 30% but maintained the study population constant 17 , 22 .…”
Section: Methodsmentioning
confidence: 99%